Hybrid online-flipped learning pedagogy for teaching laboratory courses to mitigate the pandemic COVID-19 confinement and enable effective sustainable delivery: investigation of attaining course learning outcome - Ahmed M. Elkhatat (14152314) (2022)
Since the early spring of 2020, the coronavirus pandemic (COVID-19) outbreak has hindered traditional face-to-face teaching and hands-on, traditional delivery of laboratory courses, forcing universities to migrate from the traditional way of teaching to a remote online approach. Although few studies addressed the pandemic's impact on educational outcomes, no studies are found to investigate the impact of the remote online teaching approach on laboratory courses. This paper highlights the impact of the online teaching approach, coupled with flipped learning pedagogy, as a substitute for traditional laboratories. The course learning outcomes and assessment tools are analyzed and discussed for 46 students enrolled in the Unit Operations Laboratory course in the chemical engineering program at Qatar University. Results show that the course learning outcomes are achieved effectively using the hybrid online-flipped learning pedagogy, which can be considered for computerized traditional laboratories as a moderation solution to alleviate pandemic COVID-19 confinement on learning outcome. This methodology can also be sustained in the future to facilitate the teaching of such lab courses, even in normal conditions, to optimize the resources and avail the delivery of such courses to a larger audience who may have various obstacles to attending traditional lab courses. Other Information Published in: SN Social Sciences License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s43545-021-00117-6